Serum Levels of Asymmetric Dimethylarginine and Apelin as Potential Markers of Vascular Endothelial Dysfunction in Early Rheumatoid Arthritis - Manuela Di Franco; Francesca Romana Spinelli; Alessio Metere; Maria Chiara Gerardi; Virginia Conti; Francesca Boccalini; Cristina Iannuccelli; Francesco Ciciarello; Luciano Agati; Guido Valesini (Mediators of Inflammation)
Objectives. Impaired endothelial function represents the early stage of atherosclerosis, which is typically associated with systemic inflammatory diseases like rheumatoid arthritis (RA). As modulators of endothelial nitric oxide synthase expression, asymmetric-dimethylarginine (ADMA) and apelin might be measured in the blood of RA patients to detect early atherosclerotic changes. We conducted a prospective, case-control study to investigate serum ADMA and apelin profiles of patients with early-stage RA (ERA) before and after disease-modifying antirheumatic drug (DMARD) therapy. Methods. We enrolled 20 consecutively diagnosed, treatment-naïve patients with ERA and 20 matched healthy controls. Serum ADMA and apelin levels and the 28-joint disease activity scores (DAS28) were assessed before and after 12 months of DMARDs treatment. All patients underwent ultrasonographic assessment for intima-media tickness (IMT) evaluation. Results. In the ERA group, ADMA serum levels were significantly higher than controls at baseline (P=0.007) and significantly decreased after treatment (P=0.012 versus controls). Baseline serum apelin levels were significantly decreased in this group (P=0.0001 versus controls), but they were not significantly altered by treatment. IMT did not show significant changes. Conclusions. ERA is associated with alterations of serum ADMA and apelin levels, which might be used as biomarkers to detect early endothelial dysfunction in these patients.